2014
DOI: 10.1016/j.canep.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Red meat and fruit intake is prognostic among patients with localized cutaneous melanomas more than 1mm thick

Abstract: Background As the 10-year mortality for localized cutaneous melanoma more than 1.00 mm thick approaches 40% following complete resection, non-therapeutic interventions that can supplement recommended active surveillance are needed. Although guidelines recommending nutrition, physical activity and tobacco cessation for cancer survivors have been published, data describing their associations with melanoma survivorship are lacking. Methods Analysis of modifiable lifestyle behaviors collected on the 249 cases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…The only study in melanoma patients, the Connecticut Skin Self-Examination Case-Control Study, found no association between the daily consumption of fruit or weekly consumption of green salad before diagnosis and site-specific cancer mortality ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only study in melanoma patients, the Connecticut Skin Self-Examination Case-Control Study, found no association between the daily consumption of fruit or weekly consumption of green salad before diagnosis and site-specific cancer mortality ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…The main cause for this classification was the concern of changes in exposure status among patients. In addition, minor reasons reducing the quality of studies were observed: bias due to confounding ( 40 , 41 , 57 ), bias in classification of exposures ( 39 , 40 , 42 , 47 , 48 , 56 ), and bias in selection of the reported results ( 36 , 39 , 41 , 42 , 57 , 61 ) ( Supplemental Table 7 ). More details about the items considered in both the ROBINS-E and the STROBE-nut scale are provided as supplementary material ( Supplemental Tables 8 and 9 , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In one case–control study, Gould Rothberg et al . found no evidence of an association between smoking at the time of melanoma diagnosis and worse 10‐year survival outcomes in 249 patients with melanoma >1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…9 The aim of this study was to use propensity score matching to determine whether smoking is associated with a higher risk of SLN metastasis or worse prognosis in patients with cutaneous melanoma. Table 1 Characteristics of patients with cutaneous melanoma depending on smoking habit before and after matching based on propensity score (23) 26 (23) 29 (25) 26 (23) 27 (24) 38 (22) 39 (22) Others 15 (13) 96 (21) 27 (16) 15 (13) 19 (17) 15 (13) 13 (12) 29 (17) 27 ( tertiary hospital in Valencia, Spain. We selected consecutive patients whose medical records mentioned smoking status.…”
Section: Introductionmentioning
confidence: 99%
“…A single case-control study from the Unites States has reported significantly elevated RR of 1.84 for cutaneous melanomas associated with red meat intake of more than once weekly compared with less than once a week (Gould Rothberg, Bulloch, Fine, Barnhill, & Berwick, 2014). Other factors identified as significantly associated with melanoma occurrence were age, hair color and fruit consumption; incidence increased with age and decreased with greater fruit intake.…”
Section: Epidemiology Of Meat and Cancermentioning
confidence: 92%